Getting it All Down: Disintegration and Integration in B. S. Johnson’s The Unfortunates - Ben Winsworth (Angles)
B. S. Johnson’s infamous ‘book in a box’ The Unfortunates (1969) is more than an experiment in form. The unbound signatures of the novel we are invited to shuffle into any order before reading are not only expressive of Johnson’s belief in the random nature of existence, but more specifically, as his friend Zulfikar Ghose noted, the randomness that is in the nature of cancer. The box of tricks aspect to the novel has often occluded the human story contained within it: the death of the narrator’s/Johnson’s friend Tony from cancer, and his attempt to fulfil his final promise to ‘get it all down mate’ and so write with unflinching honesty about the experience and its aftermath. Critics have either tended to dismiss the story of the lives contained within The Unfortunates as mundane and boring, or as failing to match up to the radical format of the text. However, in this article I will be reconsidering the relationship between form and content, arguing that the narrator’s melancholy observation of life and descriptions of the slow and painful death of his friend are more than an adequate match for the structure/non-structure of the novel. Tony’s physical disintegration and the narrator’s depressive state of mind, as he reflects back upon the death of his friend and its consequences, find an ideal habitat in the fragmentary nature of The Unfortunates. I will also be attempting to show how the more formal, physical aspects of the novel — the box, the first and final part, the unnumbered signatures — facilitate the dynamics of grief in providing a space for Johnson’s interior monologues to take whatever experimental shape and direction they choose, while also working to hold and contain the emotional and intellectual conflicts within them and thus guard against complete disintegration. I shall be arguing that within this particular interplay there is a movement towards integration that, while it doesn’t give Johnson any wholly positive insights, is at the very least a gesture towards the therapeutic for both himself and the reader.